Treatment of Tricuspid Regurgitation at Subvalvular Level: Hemodynamic and Morphological Assessment in Ex-Vivo Beating Heart Model. Issue 1 (2nd January 2020) - Jaworek, Michal; Pappalardo, Omar A.; Selmi, Matteo; Gelpi, Guido; Romagnoni, Claudia; Lucherini, Federico; Ajmone-Marsan, Nina; Redaelli, Alberto; Fiore, Gianfranco B.; Votta, Emiliano; Antona, Carlo; Vismara, Riccardo
ABSTRACT: Background: Functional tricuspid regurgitation (FTR) treatment is challenging and most therapies targeting tricuspid valve (TV) annulus have shown limited durability with high rate of residual and recurrent regurgitation. In fact, right ventricular (RV) dilatation, which is another important determinant of FTR, remains unaddressed with these procedures. The aim of this study was to assess the effects of RV free wall approximation (FWA) toward the septal wall in an ex-vivo pulsatile model of FTR. Methods: FWA was simulated in 15 porcine right hearts by approximating RV free wall at the anterior papillary muscle level toward the septal wall in three different directions. Results: The treatment induced 19% decrease of regurgitation fraction with respect to pre-treatment and changes in TV morphology including reduction of TV tenting volume (up to 47%) and annulus size (up to 18%) as assessed via 3D computational reconstructions from echocardiographic volumetric data. The procedure success was significantly correlated (R 2 = 0.91) with TV annulus size ( p = 0.02) when corrected for pre-treatment cardiac output. Conclusions: As evaluated in the FTR experimental model, FWA significantly reduced TV regurgitation, leaflet tenting and annular dimension. Concomitant annular stabilization could improve the results as the pre-treatment dimension of TV annulus had an impact on FWA outcome.